Applied mathematical model for a heat transfer (Periodicals of Engineering and Natural Sciences, 2021)
It is implicit for some time ago, that the radiative magneto hydrodynamic stands for an interacting between a radiation field and magneto hydrodynamic (MHD) field that is concerned with interacted electrical conducting fluids and electromagnetic field. An accurate solution to the heat transfer equation is obtained by calculating the radiant heat emission in the boundary layer MHD because of the eccentric rotations of the pore disk and the fluid for long time. It is found that the asymptotic solution is present in both the cases of suction and blowing states, whereas no such solution exists for the blowing state in the absence of radiative emission of heat. The heat transfer rate at the disk has been determined and the condition is gotten for the heat to flow from the liquid to the disk.